Bildgeschichte untuk Keterampilan Menulis Bahasa Jerman Siswa Kelas XI IPA 3 SMAN 1 Menganti - MEGA PRATIWI, YUNITA (LATERNE, 2013)
Writing, in teaching-learning process of German needs completeness in selecting vocabulary, spelling, coherence between sentences and grammar. Therefore, teacher should apply a method and a media to convey the focus material for writing skill. Bildgeschichte is one of the alternatives of teaching-learning model. The research problems in this study are: (1) How is the implementation of Bildgeschichte in writing skill of German for eleventh grade students of science class 3 of SMAN 1 Menganti? (2) How is the result of the study of eleventh grade students of science class 3 of SMAN 1 Menganti toward the implementation of Bildgeschichte in writing skill of German? The objectives of this study are: (1) the implementation of Bildgeschichte in writing skill of German language for the eleventh graders of science class 3, SMA Negeri 1 Menganti. (2) the result of the study of eleventh graders of science class 3, SMA Negeri 1 Menganti toward the implementation of Bildgeschichte in writing skill of German language. The advantage of this research is giving a new teaching-learning model which is Bildgeschichte. Bildergeschichte is excellent and suitable to direct or instruct students’ mind in the writing process, because Bildergeschichte describe an action. Picture and action are also interpreted subjectively, while at the same time Bildergeschichte gives enough an imagination space so that there is an individual solution. This research belongs to qualitative research. The data is in form of data analysis in descriptive qualitative. The result of this research is (1) Implementation; (a) picture 1 is in the form of family picture. In the teaching-learning process, the researcher showed a picture. The researcher also gave an example by telling about her family. Then, researcher pointed some students to tell about their families. She also used Bildgeschichte in the written test. (b) Picture 2 is in the form of job of a family member and there will be some clue points around the picture. Researcher showed to the students and gave a sentence as an example, then some of the students continue the next sentences. On the test, students also should tell it in written form. (c) picture 3 are some pictures show family’s activities which have a story and related each other. In the teaching and learning process, researcher showed some pictures and gave a sentence as example and 2 students would continue the next sentences. Then, the students must continue telling about the pictures in written form. (2) the result of the study: The average score of the test 1 is 79,1’ the average score of the test 2is 80,9; the average score of the test 3 is 92,8. From those three tests, it can be concluded that students’ result of study is above the average. Researcher hopes the next research is to implement Bildgeschichte for speaking skill. Keywords: Bildgeschichte, Writing